2018
DOI: 10.1038/s41586-018-0577-1
|View full text |Cite|
|
Sign up to set email alerts
|

Trade-offs in using European forests to meet climate objectives

Abstract: The Paris Agreement advances forest management as one of the pathways to halt climate warming through carbon dioxide (CO 2 ) emission reduction 1 . The climate benefits from carbon sequestration from forest management may, however, be reinforced, counteracted, or even offset by concurrent management-induced changes in surface albedo, surface roughness, biogenic volatile organic compound emissions, transpiration, and sensible heat flux 2 – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
137
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(172 citation statements)
references
References 25 publications
7
137
0
6
Order By: Relevance
“…Clearing forests releases C stored in trees but it increases the Earth's albedo (reflection of solar radiation back into space) such that we now need scientific assessments of whether this leads to net cooling or warming. Luyssaert et al () assessed trade‐offs in using European forests to meet climate objectives, and found that improved C sequestration may be offset by changes in surface albedo, land surface roughness, VOC emissions, transpiration, and sensible heat flux induced by different forest management. Understanding the extent to which C sequestration through restoration within FLR can cool the planet will therefore depend on the net interplay of carbon uptake and VOC emissions, as well as albedo and transpiration differences between forest types and between different biomes.…”
Section: Stepping Up To Create a Broad Scientific Basis For Large‐scamentioning
confidence: 99%
See 1 more Smart Citation
“…Clearing forests releases C stored in trees but it increases the Earth's albedo (reflection of solar radiation back into space) such that we now need scientific assessments of whether this leads to net cooling or warming. Luyssaert et al () assessed trade‐offs in using European forests to meet climate objectives, and found that improved C sequestration may be offset by changes in surface albedo, land surface roughness, VOC emissions, transpiration, and sensible heat flux induced by different forest management. Understanding the extent to which C sequestration through restoration within FLR can cool the planet will therefore depend on the net interplay of carbon uptake and VOC emissions, as well as albedo and transpiration differences between forest types and between different biomes.…”
Section: Stepping Up To Create a Broad Scientific Basis For Large‐scamentioning
confidence: 99%
“…Scientific research will play an essential role in focusing and delivering evidence‐based knowledge to back up this larger process (as seen by recent publications cautioning that storage carbon alone does not necessarily stop climate warming; e.g. Unger ; Luyssaert et al ).…”
Section: Stepping Up To Create a Broad Scientific Basis For Large‐scamentioning
confidence: 99%
“…Land use/cover change (LUCC) can induce significant variations in land surface fluxes and water budget partitioning, thereby impacting local and regional climate [1][2][3][4][5][6][7]. The influences of LUCC in the Earth system have been a major concern for the global change assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Following the Paris Agreement [21], the European Union (EU) has committed to a 40% domestic reduction in greenhouse-gas emissions compared to 1990 levels by 2030, 25% of which is expected to come from land-use change and forestry [22]. Despite doubts about whether such efforts may have an influence on climate change mitigation [23], they will influence and already have influenced forest management decisions, and, thus, forests and forestry [24]. Forest management has long aimed for a sustainable yield of wood; however, the concept of sustainable forest management has been adjusted to also include ecological and social sustainability requirements [25].…”
Section: Introductionmentioning
confidence: 99%